THE ROLE OF SHARIA FINTECH IN IMPROVING HALAL FINANCIAL INCLUSION IN MSMES IN INDONESIA - Safarina Dewi, Ina; Hermawan Adinugraha, Hendri (Likuid Jurnal Ekonomi Industri Halal, 2023)
The revolution of Islamic financial institutions in technology has become a must because of the progress of technology and information. Collaboration with financial technology (fintech) is expected to encourage the role of sharia-based fintech lending and other sharia fintech in developing the halal product industry in Indonesia. This article aims to explain the role of Islamic fintech in increasing financial inclusion for halal MSMEs in Indonesia. A literature review is a research method. The results obtained are the role of the application of Islamic fintech in increasing financial inclusion by providing access to financing for MSMEs engaged in the halal industry, providing convenience for MSME actors in accessing various types of Islamic bank financial services and encouraging equitable access to public finances that have not been reached by financial institutions, formal and domestic halal industry players. In Indonesia, fintech has contributed to the National Strategy for Financial Inclusion.